A phosphorous-based bi-functional flame retardant for rigid polyurethane foam. (April 2021) - Wang, Jingyu; Xu, Bo; Wang, Xiangdong; Liu, Yanting
Highlights: The bi-functional flame retardant (PDEP) containing phosphophenanthrene (DOPO) and a phosphate (DEP) moieties was chemically incorporated into the network of RPUF. PDEP could continuously release phosphorus free radicals with quenching effect at different temperatures, causing a continual flame-inhibition effect for matrix combustion. EG was bonded by the viscous species from PDEP resulting in compact and integrated char layers and thus brought protective barrier effect to RPUF composite. PDEP/EG system exert flame-retarding functions in both condensed and gaseous phase for a prolonged period of time. Abstract: A bi-functional flame retardant for rigid polyurethane foam (RPUF), denoted as PDEP, was designed and synthesized. PDEP contained two phosphorus-based moieties: phosphophenanthrene (DOPO) and a phosphate (DEP), which may exert different functions at different temperatures. DEP and DOPO moieties in sequence decomposed with increasing temperature, continuously releasing and holding high-content phosphorus-oxygen free radicals with quenching effect and producing viscous residues to bond and integrate other char species leading to high barrier effect. The flame retardant modes of action of PDEP was confirmed by experiments using thermogravimetric analysis-Fourier transform infrared (TGA-FTIR), pyrolysis-gas chromatography/mass spectrometry (Py-GC/MS), FTIR and SEM. PDEP was incorporated into RPUF system via co-cured with other polyol components. Using expandable graphite (EG) as additive-type flame retardant, an enhanced flame retardancy in RPUF was observed.